Предмет:
МатематикаАвтор:
snickers71Ответ: 1) -3; 2) -5.
Пошаговое объяснение:
Нужно знать формулу: (a + b)² = a² + 2ab + b².
1) (х + 3)² - x(x + 12) = -9x,
х² + 6х + 9 - х² - 12х + 9х = 0,
3х + 9 = 0,
3х = -9,
х = -9 : 3,
х = -3;
2) (x + 1)(3x - 2) - 3х² = 3х² - 2х + 3х - 2 - 3х² = х - 2;
если х = -3, то х - 2 = -3 - 2 = -5.
Автор:
hulketn5Добавить свой ответ
Предмет:
МатематикаАвтор:
austinОтветов:
Смотреть
Предмет:
Английский языкАвтор:
juanОтветов:
Смотреть
Предмет:
Русский языкАвтор:
dominick67Ответов:
Смотреть